From Open Access to Open Data: Collaborative work in the university libraries of Catalonia - Alcalá Ponce de León, Mireia; Anglada i de Ferrer, Lluís (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2018)
In the last years, the scientific community and funding bodies have paid attention to collected, generated or used data throughout different research activities. The dissemination of these data becomes one of the constituent elements of Open Science. For this reason, many funders are requiring or promoting the development of Data Management Plans, and depositing open data following the FAIR principles (Findable, Accessible, Interoperable and Reusable). Libraries and research offices of Catalan universities –which coordinately work within the Open Science Area of CSUC– offer support services to research data management. The different works carried out at the Consortium level will be presented, as well the implementation of the service in each university.